2022
DOI: 10.3389/fphys.2021.805646
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Responses in Copepods Are Driven Primarily by Food Intake, Not by Toxin-Producing Cyanobacteria in the Diet

Abstract: The association between oxidative processes and physiological responses has received much attention in ecotoxicity assessment. In the Baltic Sea, bloom-forming cyanobacterium Nodularia spumigena is a significant producer of various bioactive compounds, and both positive and adverse effects on grazers feeding in cyanobacteria blooms are reported. To elucidate the effect mechanisms and species sensitivity to the cyanobacteria-dominating diet, we exposed two Baltic copepods, Acartia bifilosa and Eurytemora affini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 75 publications
(103 reference statements)
0
3
0
Order By: Relevance
“…We found that with the increase of K. mikimotoi concentrations, AChE activity significantly increased, followed by a decrease ( Figure 3 ). Activated AChE activities have been also found in copepods fed on toxic cyanobacteria and several other microcrustaceans under stress [ 37 , 67 ]. AChE has been identified as a biomarker of neurotoxic contaminants in benthic copepods [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that with the increase of K. mikimotoi concentrations, AChE activity significantly increased, followed by a decrease ( Figure 3 ). Activated AChE activities have been also found in copepods fed on toxic cyanobacteria and several other microcrustaceans under stress [ 37 , 67 ]. AChE has been identified as a biomarker of neurotoxic contaminants in benthic copepods [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…SOD, CAT, and GPx comprise the first-line defense antioxidants by dismutating superoxide radicals and breaking down hydrogen peroxides and hydroperoxides to harmless molecules, respectively [ 36 ]. They are indispensable in the entire defense strategy and commonly used for oxidative status assessment in various organisms, including copepods [ 37 , 38 ]. Moreover, acetylcholinesterase (AChE), the hydrolyzing enzyme of the neurotransmitter acetylcholine, is also a well-established biomarker of various environmental stressors, including toxic algae [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation